(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article describes the established deposit (wasting a penny in the dovzhiny road to the canal that transports) was removed as a result of the investigation. On the stand, which marked the end of the transport channel, as well as the place for the expansion of the foaming device for the subsurface application machines for the protection of weeds, in the balls of the stump. One of the chemical ways to kill the growths is the subsurface introduction of chemicalization into the bowl, which transfers the active substance into the ball and applies it to the stained sour cream. The pressure is pumped into the middle of the empty tank, which is positioned under the influx of the working body. The working body for this method is formed from an arrow-shaped paw with a stable, kinematic structure, which on the fastening bracket has a channel for bringing the stump into the paw space. Between the wings of the arrow-shaped plows there is a waterproofing cap, which is a regulator of the hourly dampness of the soil. The technological process of subsurface introduction of rare chemical agents takes place during the process of destruction of the working body. The foam is fed through the channel into the space, surrounded by the plowshares of the sharp paw and the waterproofing cap. Having accumulated in the middle of this space, it expands empty. Next, the soil, scalding, redistributes the foam, destroying the bottom part into the center of the smudge, which forms. It appears for the same reason that the soil initially crumbles along the edges, and then at the center. This way, you achieve an even distribution of the stumps across the width of the smudge, which will make you squish. The technology for introducing rare chemical agents into foam balls has been introduced, and is transferred to existing machines for surface treatment of the soil of liquid working parts and a foam-generating device (foam generator). The foam-generating device consists of a compressor, a reservoir for the working medium (water dispensing chemicals and foam-creating fluid), foam-creating nozzles and pipelines. The number of working parts on machines that are transferred to vicorization for the introduction of chemicalization to the stump ball is determined by the width of the treatment (for continuous application) or the number of rows (for daily sampling).